THE ERADICATION OF MENTAL SLAVERY THROUGH AFRICAN INTELLECTUALISM OF BLACK CONSCIOUSNESS - Ndazalama Mathebuala (Journal of Social Political Sciences, 2023)
The primary goal of this study was to analyse the eradication of mental enslavement and explore solutions to mental slavery according to the conceptualization of Black Consciousness through African intellectualism.  This was achieved by exploring mental slavery and its contemporary forms, highlighting the different forms mental slavery takes, which tends to make the eradication process complex.  The study provided the conceptual framework that was prominent in informing the recommendations and how Black Consciousness should be harnessed and operationalized to psychologically emancipate black people by four African Intellectuals Biko, Fanon, Nkrumah, and Sankara. The findings of the study were based on a contemporary form of mental enslavement manifested through the notion-image of beauty skin bleaching and hair extensions. Based on the research findings, the study recommends that Black Consciousness should be part of the education curriculum where the ideology will be taught as a way of life. Furthermore, there should be collective efforts to celebrate and affirm true African identity as conceptualized by African Intellectuals.